2015
DOI: 10.1182/blood.v126.23.257.257
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Trial Testing Single Agent CUDC-907, a Novel, Oral Dual Inhibitor of Histone Deacetylase (HDAC) and PI3K: Initial Assessment of Patients with Relapsed or Refractory (RR) Diffuse Large B-Cell Lymphoma (DLBCL), Including Double Expressor (DE) Lymphoma

Abstract: DLBCL, the most common lymphoid malignancy in adults, is an aggressive form of non-Hodgkin lymphoma (NHL) with significant heterogeneity in terms of gene expression, prognosis and response to treatment. Certain histone modifications and HDAC expression patterns have been implicated in the pathobiology of DLBCL and other cancers. Aberrant PTEN/PI3K/AKT signaling is also frequently observed in a variety of human cancers including DLBCL, where loss of PTEN activity and/or activating mutations in PI3K and AKT have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…CUDC-907 is a class I-II oral double-inhibitor of HDAC and PI3K (α, β, γ) enzymes (111,220,(220)(221)(222).…”
Section: Hdac Inhibitors (Hdis)mentioning
confidence: 99%
“…CUDC-907 is a class I-II oral double-inhibitor of HDAC and PI3K (α, β, γ) enzymes (111,220,(220)(221)(222).…”
Section: Hdac Inhibitors (Hdis)mentioning
confidence: 99%
“…Indeed, this agent, CUDC-907, was shown to kill tumors cells in vitro and suppress tumor growth in vivo in DLBCL and thyroid cancer models (Kotian et al 2017, Mondello et al 2017. A first-in-man phase I study was performed in patients with relapsed or refractory lymphoma or multiple myeloma (Oki et al 2017, Younes et al 2015; https://www.clinicaltrials.gov/ identifier NCT01742988). CUDC-907 was well tolerated, a phase II trial was initiated based on the success of this trial (9 of 21 objective responses in DCBCL), and the FDA granted an orphan drug designation to CUDC-907 for the treatment of patients with DLBCL (Landsberg et al 2016).…”
Section: Co-targeting Histone Deacetylases and The Pi3k/mtor Pathwaymentioning
confidence: 99%
“…CUDC-907 was well tolerated, a phase II trial was initiated based on the success of this trial (9 of 21 objective responses in DCBCL), and the FDA granted an orphan drug designation to CUDC-907 for the treatment of patients with DLBCL (Landsberg et al 2016). Retrospective analysis of responding patients indicated that responding tumors were enriched for Myc amplification (Younes et al 2015). Preclinical studies have now shown that CUDC-907 suppresses Myc expression in DCBCL cells and tumors and that Myc suppression partially contributes to the death induced by CUDC-907 (Sun et al 2017).…”
Section: Co-targeting Histone Deacetylases and The Pi3k/mtor Pathwaymentioning
confidence: 99%